Promoting the development and approval of new traditional Chinese medicines in China: a pooled analysis of data from 2013 to 2024 - Xiaohong Long; Jie Zhang; Li Yang (Frontiers in Medicine)
The reform of the development and approval system for traditional Chinese medicines (TCMs) has been in progress for several years. This reform has restructured the registration classifications and established a distinctive evaluation and registration evidence system for TCMs. This study compiled comprehensive data on all new TCMs approved in China from January 2013 to November 2024, analyzing drug characteristics and the changes in development and review timelines before and after the reform. The focus was particularly on the evaluation and registration evidence requirements, clinical development pathways, and the application of pivotal clinical and real-world evidence in supporting TCM approvals. Between 2013 and 2024, 77 new TCMs were approved for marketing. Post-reform, there has been a gradual increase in the number of new TCMs, with a notably significant rise in ancient classic formulas. Following 2020, the establishment of the “three-in-one” evaluation and registration evidence system was implemented to accommodate the distinct characteristics of TCMs. This system revealed significant discrepancies in the registration classifications for new TCMs, particularly concerning TCM theory, human use experience, and clinical trials. These discrepancies have led to varied clinical development pathways. Importantly, the findings suggest that the marketing approval of new TCMs is no longer solely reliant on Randomized Controlled Trials. Instead, TCM theories and empirical human use experience constitute critical evidence for TCM approval. Additionally, evidence derived from real-world studies has become instrumental in supporting the marketing of TCMs. Although the review time for TCMs has significantly decreased after the reform, the overall development time has increased. Simultaneously, this article proposed specific recommendations to address the array of challenges encountered by new TCMs in the realms of development and approval.